Predictive value of CD8/FOXP3 ratio combined with PD‐L1 expression for radiosensitivity in patients with squamous cell carcinoma of the larynx receiving definitive radiation therapy. Issue 12 (18th August 2020) - Ono, Takeharu; Azuma, Koichi; Kawahara, Akihiko; Kakuma, Tatsuyuki; Sato, Fumihiko; Akiba, Jun; Tanaka, Norimitsu; Abe, Toshi; Chitose, Shun‐ichi; Umeno, Hirohito
Abstract: Background: Little is known about immune‐related radiosensitivity in patients with squamous cell carcinoma of the larynx (SCC‐L) treated with radiation therapy (RT). Methods: We retrospectively reviewed 91 patients with SCC‐L treated with RT or chemoradiation therapy and performed immunohistochemical examination to analyze PD‐L1 level on tumor cells, CD4 + tumor‐infiltrating lymphocytes (TILs), CD8 + TIL, and FOXP3 + TIL using pretreated biopsy specimens. The association between these immune‐related parameters and radiosensitivity was evaluated. Results: Multivariate analyses showed that high CD8/FOXP3 ratio combined with negative PD‐L1 expression was an independent and significant favorable predictive factor for local control, compared with the other groups. Conclusions: We showed that high CD8/FOXP3 ratio combined with negative PD‐L1 expression might be a useful biomarker of radiosensitivity in patients with SCC‐L receiving definitive RT. We propose that coassessment of CD8/FOXP3 ratio and PD‐L1 expression level in tumor cells can help predict potential radiosensitivity in patients with SCC‐L.